Fabrication and Upsetting of Al6061 Aluminum Metal Matrix Composite with Carbon Nanotube Reinforcement - Ho Lee, Chang; Gil Kang, Chung (Asian Journal of Chemistry, 2014)
This study aims to examine the fabrication and upsetting of Al6061 alloy reinforced by carbon nanotubes. The composite material that combines Al6061 powder (5-30 μm) and multiwall carbon nanotubes (MWCNTs) after the dispersion process goes through the compaction at room temperature and sintering to fabricate the billet. In addition, the upsetting process is conducted to evaluate the mechanical properties of fabricated composite specimens and improve the relative density. As for the composite, MWCNTs of 1 and 3 % volume fraction are fabricated to compare with Al6061alloy. The billet is fabricated at room temperature at the pressure level of 300, 450 and 600 MPa. It also goes through the sintering process (580, 600, 620 ºC) in an argon gas atmosphere. CNT-Al6061 composite shows a lower level of relative density than that of Al6061 alloy in the same condition. To improve the relative density of the complex material, the upsetting process is added. The fabrication and characteristics of CNTs-Al6061 composite are developed through the compaction at room temperature and through sintering and upsetting, with the mechanical properties being superior to those of Al6061 alloy. As a result, the mechanical properties of the composite increase in proportion to the compaction pressure and sintering temperature. As the amount of MWCNTs increase, however, elongation decreases.